STRATEGY TO IMPROVE THE ROLE AND EXISTENCE OF INSURANCE SHARIAH AT PT. ALLIANZ LIFE INDONESIA INSURANCE MEDAN BRANCH - Elvina Sari Damayanti; Fauzi Arif Lubis; Nurbaiti Nurbaiti (Jurnal Apresiasi Ekonomi, 2025)
This study aims to analyze how the strategy in increasing the role and existence of sharia insurance in PT Asuransi Allianz life Indonesia Medan branch. In this study using a descriptive qualitative approach. The approach used by the researcher is an empirical approach model. Primary data sources consist of informants such as employees of PT. Asuransi Allianz life Indonesia. Secondary data sources are taken from various book references, scientific journals, and written reports obtained from various references as a theoretical basis. Data were collected using observation, interview, and documentation techniques. By using SWOT analysis it can be concluded that PT Asuransi Allianz Life Indonesia has strengths (Strength) namely a wide marketing network (national and international), weaknesses (Weakness) namely that there are several leaders in terms of supervision of their agents are not optimal, also has opportunities (Opportunities) namely cooperation with sharia financial institutions, and has challenges (Threats) namely the entry of new competitors in the insurance industry. The results of this study indicate that the role of sharia insurance at this time is very much needed to prepare for future benefits, the role of insurance is also a form of worship of a Muslim to Allah SWT. Meanwhile, the way for sharia insurance to continue to exist is by educating the market through various communication media to explain the existence of sharia insurance, its advantages, benefits and cleanliness from public doubts. And for companies to develop products sustainably such as innovating sharia insurance products, improving human resources (HR), company service quality management, promotional strategies, cooperation with other institutions. Keywords :Sharia Insurance Strategy, The Role of Sharia Insurance, Allianz Life Indonesia Insurance